2012
DOI: 10.1007/s13224-012-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Preeclampsia by Midtrimester Uterine Artery Doppler Velocimetry in High-Risk and Low-Risk Women

Abstract: Objective To observe the role of uterine artery Doppler flow velocimetry at midtrimester in prediction of preeclampsia. Method 179 women carrying \16 weeks of pregnancy, with singleton fetus and without any fetal anomaly were recruited and were divided in high-risk and low-risk group. Doppler velocimetry of uterine artery was done at 24-26 weeks. Any notch in uterine artery, unilateral or bilateral, or RI [ 0.6, was considered abnormal. Women were followed up and development of preeclampsia noted. Result Sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
4
15
1
Order By: Relevance
“…Previous studies have reported that compared to women with normal pregnancies, pregnancy‐related complications such as preeclampsia, intrauterine growth restriction, and stillbirth have a higher uterine artery PI 5 , 9 , 10 , 12 . However, this study showed a lower uterine artery PI in patients with placenta accreta than in normal pregnancy and placenta previa.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Previous studies have reported that compared to women with normal pregnancies, pregnancy‐related complications such as preeclampsia, intrauterine growth restriction, and stillbirth have a higher uterine artery PI 5 , 9 , 10 , 12 . However, this study showed a lower uterine artery PI in patients with placenta accreta than in normal pregnancy and placenta previa.…”
Section: Discussioncontrasting
confidence: 82%
“…The physiologic changes of the spiral arteries lead to increased blood flow into the intervillous space, resulting in a progressive and substantial decrease in the mean uterine artery PI with gestation. On the other hand, inadequate physiologic changes are associated with an increased uterine artery PI, resulting in adverse pregnancy outcomes 12 . A histologic examination of placenta accreta specimens showed that the trophoblast had invaded the myometrium without deciduas, leading to nonseparation of the placenta and heavy bleeding 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plausible mechanism for the impact of maternal vitamin D on fetal growth is placental vascularization, which has received considerable attention in its association with fetal growth (39-41). Several observational studies have connected poor vitamin D status with higher risk of preeclampsia (7, 42), which, like fetal growth restriction, has placental origins related to angiogenesis and uterine blood flow (39, 43). Mice raised on vitamin D deficient diets have placentas with narrower fetal vessels in the placental labyrinth compared to mice fed vitamin D sufficient diets, indicating dysregulated vascularization (44).…”
Section: Discussionmentioning
confidence: 99%
“…Those results were in agreement with Coleman et al [18], who reported that UARI of > 0.58 can predict PE with a sensitivity of 91% and specificity of 42% and with Spencer et al [19] who highlighted the ability of second trimester UAPI to predict early onset PE with a sensitivity of 76% and specificity of 80%. Bhattacharyya et al [20] showed that an abnormal uterine artery flow velocity was associated with an increased relative risk of preeclampsia both in high risk and low-risk women with sensitivity and specificity of increased uterine artery RI for prediction of preeclampsia of 70 and 94.87 %, respectively and concluded that Doppler velocimetry of uterine artery at 24 weeks could be considered as a reliable screening test to predict PE in both low and high risk women. On the other hand, Myatt et al [21] reported that second trimester Doppler ultrasound indices showed a low sensitivity for detection of PE in low risk nulliparous women and Pongrojpaw et al [22] reported that mid trimester uterine artery Doppler waveform analysis cannot be used as screening test for PE in higher risk women.…”
Section: Discussionmentioning
confidence: 99%